(untitled) - Mason, R. H. P. (1972)
Offering a compelling introduction to Japan's rich culture and fascinating history for travelers, businesspeople, and students, this guide discusses the influence of China; the impact of feudalism, modernization, and imperialism; Japanese history of war and peace; and today's economy and uncertainty. Traced are the threads of history, environment, and culture that run through the centuries to explain much about the Japan of today.